2021
DOI: 10.3889/oamjms.2021.7060
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic Function Assessed by Bed Side Ultrasonography in Patients with Sepsis or Septic Shock Admitted to Intensive Care Unit

Abstract: BACKGROUND: Sepsis and septic shock are major problems faced the healthcare systems all over the world every year. The ultrasound (US) is a simple, non-invasive, easily accessible technique, and showed great accuracy in diaphragm assessment. AIM: We evaluated the diaphragmatic function assessed by US in patients with sepsis and septic shock and correlated these assessments with different parameters. MATERIALS AND METHODS: A prospective observational study carried out on 30 patients admitted to the intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In our population, respiratory rate was high, and accessory muscle used that indicated high respiratory effort was included in the inclusion criteria. However, low RDE was associated with requiring IMV, which results similar results to previous study [ 40 42 , 45 ]. Therefore, the evidence of diaphragmatic ultrasound needs evaluation and validation in requiring intubation in sepsis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our population, respiratory rate was high, and accessory muscle used that indicated high respiratory effort was included in the inclusion criteria. However, low RDE was associated with requiring IMV, which results similar results to previous study [ 40 42 , 45 ]. Therefore, the evidence of diaphragmatic ultrasound needs evaluation and validation in requiring intubation in sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, diaphragmatic evaluation may consider monitoring to choose ventilatory support to prevent worsening outcomes in delayed intubation and diaphragmatic weakness in mechanical ventilation [ 8 , 22 ]. A previous study evaluated the performance of diaphragmatic function was found low diaphragmatic excursion values associated need for IMV, prolonged IMV, and mortality in sepsis [ 45 ]. Similarly, this study found RDE was a good performance to predict IMV within 48 h and mortality.…”
Section: Discussionmentioning
confidence: 99%